Smad4 deficiency in hepatocytes attenuates NAFLD progression via inhibition of lipogenesis and macrophage polarization - Wei Yang; Xuanxuan Yan; Rui Chen; Xin Xin; Shuang Ge; Yongxiang Zhao; Xinlong Yan; Jinhua Zhang (Cell Death and Disease)
Abstract Nonalcoholic fatty liver disease (NAFLD), a major cause of chronic liver disorders, has become a serious public health issue. Although the Smad4 signaling pathway has been implicated in the progression of NAFLD, the specific role of Smad4 in hepatocytes in NAFLD pathogenesis remains unclear. Hepatocyte-specific knockout Smad4 mice (AlbSmad4−/−) were first constructed using the Cre-Loxp recombinant system to establish a high-fat diet induced NAFLD model. The role of Smad4 in the occurrence and development of NAFLD was determined by monitoring the body weight of mice, detecting triglycerides and free fatty acids in serum and liver tissue homogenates, staining the tissue sections to observe the accumulation of liver fat, and RT-qPCR detecting the expression of genes related to lipogenesis, fatty acid intake, and fatty acid β oxidation. The molecular mechanism of Smad4 in hepatocytes affecting NAFLD was therefore investigated through combining in vitro and in vivo experiments. Smad4 deficiency in hepatocytes mitigated NAFLD progression and decreased inflammatory cell infiltration. Moreover, Smad4 deficiency inhibited CXCL1 secretion by suppressing the activation of the ASK1/P38/JNK signaling pathway. Furthermore, targeting CXCL1 using CXCR2 inhibitors diminished hepatocyte lipogenesis and inhibited the polarization of M1-type macrophages. Collectively, these results suggested that Smad4 plays a vital role in exacerbating NAFLD and may be a promising candidate for anti-NAFLD therapy.